Expression of Cytokeratin 8, 18 and 19 in the Period of Late Lactation and Involution in Cow Mammary Gland - Alklay, Asuman Arkas; Topaloglu, Ugur; Celenk, Fatma; Aydin, Nursin; Bayram, Bayram; Atalar, Omer (Kafkas Univ, Veteriner Fakultesi Dergisi, 2022)
Cytokeratins are intermediate filament proteins found in epithelial cells. Specific cytokeratin expression has been suggested to mark different epithelial cell line and also to associate with mammary stem/progenitor cells. However, a comparative analysis of the expression of cytokaratins in the mammary gland during the late lactation and involution periods was limited. Here, the aim of the present study is to evaluate CK8, CK18 and CK19 expressions of the mammary gland in cows during late lactation and involution periods, immunohistochemically. The lobe and lobule structure were prominent in the mammary tissue in the late lactation period, but the amount of connective tissue started to increase, and epithelial cells found on the walls of the alveoli had different appearances based on their secretion status. The walls of the ducts were covered by simple columnar epithelial cells during late lactation. CK8 and CK18 showed strong expressions in the epithelial cells of several alveoli and ducts inside the lobes and lobules in the late lactation and involution periods. In both late lactation and involution periods, there was no CK19 expression in the mammary gland tissue. In conclusion, it was demonstrated that CK8 and CK18 were expressed in the alveolar and ductal epithelial cells of the mammary gland in cows in the late lactation and involution periods, but CK19 was not expressed. Thus, our study findings revealed the role of CK8 and CK18 in mammary epithelial differentiation and maintenance of the normal mammary epithelial layer.
İnek Meme Bezinde Laktasyon Sonu ve İnvolusyon Döneminde Sitokeratin 8, 18 ve 19 Ekspresyonu
Keywords: Mammary gland; Cytokeratin; Cow; Immunohistochemistry